Costunolide Influences Germ Tube Orientation in Sunflower Broomrape – A First Step Toward Understanding Chemotropism - Krupp, Anna; Bertsch, Barbara; Spring, Otmar (Frontiers in Plant Science, 2021)
Orobanche cumana WALLR. is a host specific root parasite of cultivated sunflower with increasing economic importance in Europe, North Africa and parts of Asia. While sesquiterpene lactones (STLs) released from sunflower roots were identified as the natural germination stimulants of O. cumana seeds in soil, the chemical nature of signals guiding the emerging germ-tube towards the host root remained unknown hitherto. We designed a bioassay which allowed observation of broomrape germination and subsequent germ-tube development in the presence of substances with putative chemotropic activity. Root exudates and sunflower oil extracts, both containing STLs in micromolar concentrations, caused positive chemotropic orientation of germ-tubes. A similar positive chemotropic effect was achieved with costunolide, one of the four STLs of sunflower present in the exudate and oil extract. In contrast, GR24, a synthetic strigolactone (SL) with germination inducing activity on O. cumana seeds, showed no effect on the germ-tube orientation. The effect of costunolide was concentration dependent and in the range of its natural micromolar occurrence in roots. We assume that a STL gradient is responsible for a stronger inhibition of elongation growth on the host-facing flank of the germ-tube compared to the far side flank. This would confer a double role of STLs from sunflower root exudates in the sunflower-broomrape-interaction, namely as germination stimulants and as chemotropic signals.